Taxonomic review of the genus Tetranema (Scrophulariaceae) - Mendez-Larios, Isidro; Villaseñor, Jose Luis (Instituto de Ecología, A.C., 1995)
A taxonomic revision of Tetranema (Scrophulariaceae), a genus of four species distributed in eastern and southeastern Mexico, Guatemala and Honduras, is presented. A cladistic analysis, based on morphological characters, explores phylogenetic relationships among species. Distribution maps, descriptions and synonymy for each of the species, as well as a key to their idenfication are provided.